Angelica polysaccharide promotes proliferation and osteoblast differentiation of mesenchymal stem cells by regulation of long non-coding RNA H19: An animal study. Issue 7 (July 2019) - Xie, Xiaoyan; Liu, Miao; Meng, Qiang
Abstract : Objectives: Osteoporosis is a systemic bone metabolic disease, which often occurs among the elderly. Angelica polysaccharide (AP) is the main component of angelica sinensis, and is widely used for treating various diseases. However, the effects of AP on osteoporosis have not been investigated. This study aimed to uncover the functions of AP in mesenchymal stem cell (MSC) proliferation and osteoblast differentiation. Methods: MSCs were treated with different concentrations of AP, and then cell viability, Cyclin D1 protein level, and the osteogenic markers of runt-related transcription factor 2 (RUNX2), osteocalcin (OCN), alkaline phosphatase (ALP), bone morphogenetic protein 2 (BMP-2) were examined by Cell Counting Kit-8 (CCK-8) and western blot assays, respectively. The effect of AP on the main signalling pathways of phosphatidylinositol 3-kinase (PI3K)/protein kinase B (AKT) and Wnt/β-catenin was determined by western blot. Following this, si-H19#1 and si-H19#2 were transfected into MSCs, and the effects of H19 on cell proliferation and osteoblast differentiation in MSCs were studied. Finally, in vivo experimentation explored bone mineral density, bone mineral content, and the ash weight and dry weight of femoral bone. Results: The results revealed that AP significantly promoted cell viability, upregulated cyclin D1 and increased RUNX2, OCN, ALP, and BMP-2 protein levels in MSCs. Moreover, we found that AP notably activated PI3K/AKT and Wnt/β-catenin signalling pathways in MSCs. Additionally, the relative expression level of H19 was upregulated by AP in a dose-dependent manner. The promoting effects of AP on cell proliferation and osteoblast differentiation were reversed by H19 knockdown. Moreover, in vivo experimentation further confirmed the promoting effect of AP on bone formation. Conclusion: These data indicate that AP could promote MSC proliferation and osteoblast differentiation by regulating H19. Cite this article : X. Xie, M. Liu, Q. Meng. Angelica polysaccharide promotes proliferation and osteoblast differentiation of mesenchymal stem cells by regulation of long non-coding RNA H19: An animal study. Bone Joint Res 2019;8:323–332. DOI: 10.1302/2046-3758.87.BJR-2018-0223.R2.